Biomechanical Simulation of Sugita Aneurysm Clip: Reverse Engineering Approach using Metal 3D-Printing. Issue 1 (March 2021) - Asmaria, T; Zuchruf, Y M; Triwardono, J; Rokhmanto, F; Erryani, A; Lestari, F P; Dwijaya, M S; Kartika, I; Wahjoepramono, E J; Pramono, A W
Abstract: Aneurysm clips have helped hundred cased for brain abnormalities including the haemorrhagic strokes over the world, including Indonesia. As one of the contributors of a hundred trillion rupiahs for medical devices imports each year, the technology of aneurysm clips is expected to be self-manufactured. However, there is no study if the process can be done in the whole country of Indonesia. This study aims to conduct a preliminary study by using an approach of reverse engineering for the Sugita aneurysm clips as an effort to independently provide domestic medical devices. The methods consist of a 3D scanning process, a 3D printing process, biomechanical simulations, and tension measurements. The clip has been scanned and printed using SS316L and Ti6Al4V. Biomechanical simulations reach 0.054 GPa for the von Misses stress and deformation number of 4.0302E-6 mm. The tension measurement on the 3D-printed clip shows identical range numbers compared to the original clip. The experiment concludes that the acquired Sugita aneurysm clip can be reversed using a 3D metal printing and shows a significant similarity on geometrical analysis.